ANALYSIS OF FACTORS AFFECTING THE CAPITAL STRUCTURE AND PROFITABILITY IN INDONESIANS MANUFACTURING COMPANY YEAR 2009 2013 - Hamidah Hamidah (Jurnal Keuangan dan Perbankan, 2016)
This study is to determine the effect of variable business risk, liquidity, growth and tangibility asset directlyagainst leverage, as well as the influence of these variables directly to the profitability and indirectly moderatedby leverage variable. The population studies were all manufacturing companies listed in Indonesia StockExchange, during year 2009 up to 2013. The sample was determined by using purposive sampling method,with the specified criteria obtained 88 sample of companies in Indonesia. This Research used financial statementsdata issued by the Indonesian Stock Exchange, and used path analysis techniques to answer the hypothesisof the study by using software SPSS 20.The result shows that business risks, companies, liquidity and asset tangibility grow significantly and havenegative effect on leverage. Liquidity and companies growth dont have positive effect on profitability as wellas asset tangibility and leverage, while business risk have positive effect. For the indirect effect indicates therewere indirect influences on profitability were tangibility asset and liquidity. For further research, the samplecan be used not only in the manufacturing sector but also other sectors.Keywords: profitability, leverage, business risk, liquidity, growth, asset tangibility, path analysis